Survival and complications in splenic trauma: surgical versus non-surgical outcomes - Kassis, Mohamad B. A. (International Surgery Journal, 2024)
Background: Splenic injuries are common in trauma patients, accounting for approximately 20% of abdominal trauma cases. Given the spleen’s anatomical vulnerability and the critical nature of timely intervention, understanding the impact of different management strategies on patient outcomes is essential. This study investigates the effectiveness of surgical versus non-surgical management in splenic trauma, focusing on mortality and complication rates based on injury severity and patient stability. Methods: A retrospective cohort study was conducted, analyzing trauma patients with splenic injuries admitted to Azahra Hospital from January 2020 to December 2022. Medical records were reviewed to collect data on patient demographics, injury severity, management strategies, and clinical outcomes. Results: A total of 50 patients were included in the study, with 32 undergoing operative treatment. The analysis revealed that operative treatment was associated with significantly lower mortality rates (21% in surgical cases versus 4.3% in non-operative cases) and fewer complications (p<0.001). A positive correlation was observed between splenic injury stage and mortality, as well as between hemodynamic instability and complications. Conclusions: Initial findings indicated higher mortality and complication rates in surgical patients; however, after controlling for confounding variables, operative treatment demonstrated an unexpected inverse correlation with both mortality and complications. This emphasizes the importance of personalized management approaches in splenic trauma to optimize patient outcomes.